Manajemen Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Di Sekolah - Iis Aisul Istianah; Ahmadi, Ahmadi; Siminto (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2025)
Principal leadership management is the ability possessed by the principal as the leader of the school or educational institution in managing or influencing teachers and staff to be willing to carry out their tasks and responsibilities with full confidence and enthusiasm to achieve the school's predetermined goals. The purpose of this study is to determine: (1) the principal's program planning in improving the quality of education, (2) the implementation of the principal's program in improving the quality of education, and (3) what obstacles are encountered in implementing the principal's program in improving the quality of education. This study uses a qualitative research approach with a qualitative descriptive method. The subjects of the study are: principals, teachers, administrative staff and students. Data collection uses observation, interviews and documentation. Data analysis includes: data reduction, data presentation and data verification (drawing conclusions), while to test the validity of the data using data triangulation and member check. This research produced the following findings: (1) School program planning includes: teaching programs, including: teacher needs, distribution of teaching tasks, procurement of textbooks, teaching tools and demonstration tools, procurement or development of school laboratories, procurement or development of school libraries, learning outcome assessment systems, and curricular activities; (2) Implementation of school programs, namely: strategies applied to achieve improvements in the quality of education, including: program socialization, SWOT analysis, problem solving, quality improvement, and monitoring and evaluation of the implementation of school programs; and (3) Obstacles in school program planning, including lack of community participation and economic difficulties so that their support for school management is also low. It is expected that supervisors can direct and supervise school principals in improving the quality of education regarding school program planning, program implementation and obstacles faced appropriately, effectively and efficiently so that the quality of education in the school can be improved properly. Keywords: Management; Principal Leadership; and Quality of Education.